Study on performance of partial combustion unit at direct reduction plant by using CFD - Norliyana, Erain (2012)
Partial Combustion (PC) system is one of the very important systems in Direct Reduction Plant (DRP) which allows increasing the production rate, quality of Direct Reduced Iron (DRI), and diminishing the natural gas consumption. This system is consists of one transfer line with two oxygen lances placed in horizontal position in the middle of transfer line. The transfer line is situated in between the gas heater and reactor. The objectives of this study are to validate the temperature profile of simulated result with current installation in real plant and to define more accurate temperature reading of Partial Combustion system. Besides, the other objective of this study is to propose new position of oxygen lances installed. To modify an existing system, it actually requires high cost. Hence, in this study a simulation was performed in order to solve the problem exists. Computational Fluid Dynamic (CFD) is a tool used in this simulation which consists of GAMBIT and FLUENT. Volume meshing in GAMBIT is an important part to be considered before doing simulation in FLUENT as a solver. Parametric study was proposed to give more accurate temperature reading. New model of transfer line with considering refractory is believed can give better result for the same purpose. In real plant, the transfer line was covered by the two layers of refractory brick. For further modification, new position of oxygen lances also introduced to increase the temperature of reactor inlet. Increasing of temperature at reactor inlet can increase the production rate and will increase the tubes life in heater. For this purpose, the modified of oxygen lances position give better performance than existing position. From this study, the temperature profile of Partial Combustion system can be validated thus can give better performance for this system.